ANALISIS KESULITAN SISWA PADA PEMAHAMAN TEKS DEKSKRIPTIF KELAS V SD 1 BARONGAN - Stelawati, Yuyun; Nuraini Arifin, Septiani; Ardana Riswari, Lovika (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Reading is a skill that elementary school students must master, and reading comprehension of expository text is very important especially in grade five. In the implementation process, there are still some people who do not know how to read the instructions. Difficulties in reading usually make it difficult to learn further in class. The research that analyzed the difficulty of reading and comprehending expository text was conducted on grade V students in one of the Kudus cities. The research method used was qualitative research. Data collection techniques were observation, test, and documentation. The research tools used in this study were descriptive texts, observation sheets, and other supporting documents. Based on the results of the study, most of the students' ability to read and understand expository texts reached the competency category, namely 60% or 22 students had reached the competency. Some students (up to 10 students) still do not know how to complete expository reading comprehension activities. The biggest difficulty faced by students is the ability to read and understand descriptive text in this study, but it is not significant